Development and validation of a ready-to-use score to prioritise medication reconciliation at patient admission in an orthopaedic and trauma department. Issue 5 (8th December 2020) - Vallecillo, Thibault; Slimano, Florian; Moussouni, Marie; Ohl, Xavier; Bonnet, Morgane; Mensa, Christophe; Hettler, Dominique; Kanagaratnam, Lukshe; Mongaret, Céline
Abstract : Objective: Medication reconciliation (MR) is recognised as an important tool in preventing medication errors such as unintentional discrepancies (UDs). The aim of this study was to identify independent predictive factors of UDs during MR at patient admission to an orthopaedic and trauma department. The secondary objective was to build and validate a ready-to-use score to prioritise patients. Method: A retrospective study was performed on 3.5 years of pharmacist-led MR in the orthopaedic and trauma department of a large university teaching hospital. Independent predictors of UD were identified by multivariable logistic regression. A priority score to identify patients at risk of at least one UD was constructed from the odds ratios of the risk factors, and validated in a separate cohort. Performance was assessed with sensitivity, specificity, C-statistic and Hosmer-Lemeshow goodness-of-fit. Results: In total, 888 patients were included and 387 UDs were identified, mainly drug omissions (65.1%). Five independent predictors of UD were identified: age >75 years (OR 2.05, 95% CI 1.41 to 3.00; p<0.001), admission during school holidays (OR 1.69, 95% CI 1.17 to 2.44; p=0.005), female gender (OR 2.20, 95% CI 1.53 to 3.16; p<0.001), emergency hospitalisation (OR 2.05, 95% CI 1.45 to 2.92; p<0.001), and ≥5 medications on the best possible medication history (BPMH) (OR 3.29, 95% CI 2.20 to 4.94; p<0.001). Based on these predictors, a priority score ranging from 0 to 10 was built and internally and externally validated (C statistic 0.72, 95% CI 0.67 to 0.76). Conclusions: This study confirms the high prevalence of UD in patients admitted to orthopaedic and trauma surgery departments. Five independent predictive factors of UD during MR were identified (female gender, emergency hospitalisation, hospitalisation during school holidays, age ≥75 years, and ≥5 medicines on the BPMH). The developed risk score will help to prioritise MR among patients at risk of medication error and is ready-to-use in other orthopaedic and trauma departments.